NATIONAL DEFENSE AS A FORM OF YOUTH PARTICIPATION IN STRENGTHENING NATIONAL RESILIENCE - Bambang Yuniarto; Ahmad Asro Abkari; Wafa Lathifah Ilmiyah; Novi; Naili Nur Fauziyah; Ridho Abdul Muhfid (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to analyze national defense as a form of youth participation in strengthening Indonesia’s national resilience. The main problem addressed is the low awareness among young generations regarding their role in maintaining national stability and security amidst globalization, transnational ideological threats, and rapid technological advancement. The research employs a descriptive qualitative approach using literature review and policy analysis related to youth involvement in the total defense system. Data were collected from official documents, academic literature, and previous studies. The results indicate that active youth participation in social, educational, and civic defense programs significantly contributes to strengthening national resilience in ideological, sociocultural, and security dimensions. Therefore, enhancing youth capacity and awareness of national defense is a crucial factor in building a strong, adaptive, and sustainable national resilience capable of responding to multidimensional threats.